A possible mechanism for PTSD symptoms in patients with traumatic brain injury: central autonomic network disruption - Williamson, John B.; Heilman, Kenneth M.; Porges, Eric; Lamb, Damon; Porges, Stephen W. (Frontiers in Neuroengineering, 2013)
Patients with traumatic brain injuries (TBI) often develop Post Traumatic Stress Disorder (PTSD). This syndrome, defined and diagnosed by psychological and behavioral features, is associated with symptoms such as anxiety and anger with an increase of arousal and vigilance, as well as flashbacks and nightmares. Many of these features and symptoms observed in PTSD may be in part the result of altered autonomic nervous system (ANS) activity in response to psychological and physical challenges. Brain imaging has documented that TBI often induces white matter damage to pathways associated with the anterior limb of the internal capsule and uncinate fasciculus. Since these white matter structures link neocortical networks with subcortical and limbic structures that regulate autonomic control centers, injury to these pathways may induce a loss of inhibitory control of the ANS. In this review, the autonomic features associated with PTSD are discussed in the context of traumatic brain injury. We posit that TBI induced damage to networks that regulate the ANS increase vulnerability to PTSD. The means by which the vulnerability can be measured and tested are also discussed.